Effect of Lard or Plus Soybean Oil on Markers of Liver Function in Healthy Subjects: A Randomized Controlled-Feeding Trial - Liu, Zhiyuan; Yuan, Jihong; Wen, Ping; Guo, Xiaofei; Li, Kelei; Wang, Yinpeng; Liu, Ruirui; Guo, Yanjun; Li, Duo (Foods, 2023)
Humans have consumed lard for thousands of years, but in recent decades, it has become much less popular because it is regarded as saturated fat. Animal studies showed that lard plus soybean oil (blend oil) was more advantageous for liver health than using either oil alone. This study aims to assess the effects of blend oil on liver function markers in healthy subjects. The 345 healthy subjects were randomized into 3 isoenergetic diet groups with different edible oils (30 g/day) (soybean oil, lard, and blend oil (50% lard and 50% soybean oil)) for 12 weeks. The reductions in both aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were greater in the blend oil group than in the two other groups (p = 0.001 and <0.001 for the interaction between diet group and time, respectively). The reductions in AST and ALT in the blend oil group were more significant compared with those in the soybean oil group (p < 0.001) or lard group (p < 0.001). There were no significant differences in the other liver function markers between the groups. Thus, blend oil was beneficial for liver function markers such as AST and ALT compared with soybean oil and lard alone, which might help prevent non-alcoholic fatty liver disease in the healthy population.